A study of histopathological spectrum of non-malignant breast lesions - Dr. Alpesh M. Maru; Dr. Chiragkumar B. Menapara (Tropical Journal of Pathology and Microbiology, 2018)
Background: Breast Lesions include a variety of Non-malignant and malignant lesions sometimes producing diagnostic difficulty for both Clinicians as well as Pathologists. In certain cases, histopathological examination, particularly microscopy is the only way to reach to the final diagnosis, so our present study is undertaken to know about the Spectrum of variousnon-malignant breast lesions and Frequency of their occurrence.Materials & Methods: The present study is carried out in the Department of Pathology, GMERS Medical College-Junagadh from September 2015 to August 2018.Excisional and incisional breast biopsies as well as lumpectomy specimens from surgical department have been evaluated both grossly and microscopically for this present study.Results: Out of 200 cases studied during last 3 years, 155 cases belong to non-malignant (non-neoplastic and benign) lesions while 45 cases belong to malignantlesions (breast cancers). The incidence of non-malignant breast lesions is found to be 77.50 % of all breast lesions. Out of all non-malignant breast lesions, Fibroadenoma is found to be the commonest one (Total 75 cases, 48.39%) followed by Fibrocystic Disease found in 15 cases (9.68%).Conclusion: Non-malignant breast lesions include a variety of inflammatory lesions, benign tumors and tumor like conditions. Histopathological evaluation becomes necessary for such cases and plays a pivot role in their final diagnosis.